Impact of planned delivery mode on neonatal outcomes and costs in twin pregnancies in KenyaAJOG Global Reports at a Glance - Fred O. Omondi, MBChB; Meghan K. Murphy, DO; Moselle M. Stark, MD; Cheryl B. Cowles, MD; Phillip C. Greig, MD; Benoît J. Ndikumana, MMed (Obs & Gyn); Robert K. Parker, MD, MPH (Elsevier, 2024)
Background: Twin pregnancies are associated with higher risks of adverse neonatal outcomes compared to singleton pregnancies. The choice of delivery mode, when twin A presents cephalic, remains a subject of debate. In low- and middle-income countries, where healthcare resources are limited, the decision on the mode of delivery is even more critical. Objective: To evaluate the neonatal outcomes and the hospital costs of planned vaginal delivery compared to cesarean section (CS) in twin pregnancies with twin A presenting cephalic at Tenwek Hospital, Kenya. Study Design: This retrospective cohort study analyzed data from all twin deliveries at Tenwek Hospital, Kenya from, April 1, 2017, to March 30, 2023. Maternal data, mode of delivery, and neonatal data were collected from delivery logs, electronic health records, and neonatal records. Neonatal outcomes were a composite of either Appearance, Pulse, Grimace, Activity, and Respiration score less than seven at 5 minutes, neonatal intensive care unit admission, resuscitation, birth trauma, or neonatal complications, including death before discharge from the hospital. A logistic regression model was created to assess the impact of the planned mode of delivery on neonatal outcomes, controlling for antenatal care clinic visits, noncephalic presentation of twin B, and birth weight category. Results: The study included 177 twin deliveries: 129 (72.9%) were planned as vaginal deliveries and 48 (27.1%) were planned for CS. Among the planned vaginal deliveries, 66 (51.2%) experienced adverse outcomes, compared to 14 (29.2%) in the CS group (P=.009). Logistic regression showed that the odds of adverse outcomes were 0.35 times lower in the CS group compared to the planned vaginal delivery group (95% CI: 0.15-0.83; P=.017). The average total hospital costs for planned vaginal delivery were 104,608 Kenya Shillings (standard deviation 111,761) compared to 100,708 Kenya Shillings (standard deviation 75,468) for CS (P=.82). Conclusion: Planned cesarean deliveries in twin pregnancies with twin A presenting cephalic at Tenwek Hospital were associated with fewer adverse neonatal outcomes compared to planned vaginal deliveries. There was no significant difference in hospital costs. These findings raise the question of the safest mode of delivery for patients in a resource-constrained setting.